From IL-17 to IFN-γ in inflammatory skin disorders: Is transdifferentiation a potential treatment target? - Belpaire, Arno; van Geel, Nanja; Speeckaert, Reinhart (Frontiers in Immunology, 2022)
The targeted inhibition of effector cytokines such as interleukin 17 (IL-17) in psoriasis and IL-13 in atopic dermatitis offers impressive efficacy with a favorable side effect profile. In contrast, the downregulation of interferon gamma (IFN-γ) in T helper (Th) 1-dominant skin disorders may lead to more adverse events, given the crucial role of IFN-γ in antiviral and antitumoral immunity. Modulating Th17 and Th2 cell differentiation is performed by blocking IL-23 and IL-4, respectively, whereas anti-IL-12 antibodies are only moderately effective in downregulating Th1 lymphocyte differentiation. Therefore, a targeted approach of IFN-γ-driven disorders remains challenging. Recent literature suggests that certain pathogenic Th17 cell subsets with Th1 characteristics, such as CD4+CD161+CCR6+CXCR3+IL-17+IFN-y+ (Th17.1) and CD4+CD161+CCR6+CXCR3+IL-17-IFN-y+ (exTh17), are important contributors in Th1-mediated autoimmunity. Differentiation to a Th17.1 or exTh17 profile results in the upregulation of IFN-y. Remarkably, these pathogenic Th17 cell subsets are resistant to glucocorticoid therapy and the dampening effect of regulatory T cells (Treg). The identification of Th17.1/exTh17 cells in auto-immune disorders may explain the frequent treatment failure of conventional immunosuppressants. In this review, we summarize the current evidence regarding the cellular plasticity of Th17 cells in inflammatory skin disorders. A deeper understanding of this phenomenon may lead to better insights into the pathogenesis of various skin diseases and the discovery of a potential new treatment target.